Sejak Indische sampai Indonesia - Kartodirdjo, Sartono, 1921-; Dharmawan, Bagus (Jakarta : Penerbit Buku Kompas, 2005)
History of sociopolitical conditions in Indonesia; collection of articles previously published in Kompas daily from 1982 to 2000
Includes index
Keywords: Nationalism -- Indonesia -- History; Indonesia -- History -- Politics and government